2013
DOI: 10.1016/j.rehab.2013.07.785
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocioprofessional and familial becoming of formers Buruli ulcer patients in Benin

Abstract: After returning home, former UB patients suffered of severe psychosocioprofessional and familial repercussions that suggested an organization of their home monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In BUD management, seeking early complete medical intervention lowers the risk of permanent functional limitations and its associated impact on quality of life [ 2 ] and psychological co-morbidities [ 11 , 12 ]. Caregivers narrated how finances and non- availability of simple logistic support became barriers to accessing healthcare for their sick relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In BUD management, seeking early complete medical intervention lowers the risk of permanent functional limitations and its associated impact on quality of life [ 2 ] and psychological co-morbidities [ 11 , 12 ]. Caregivers narrated how finances and non- availability of simple logistic support became barriers to accessing healthcare for their sick relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Early complete antimicrobial administration gives excellent treatment outcomes, with return to quality of life [2]. On the other hand, when medical intervention is delayed or incomplete, permanent functional disabilities and their associated stigma [10] and psychological burden ensues [11][12][13]. Exacerbating these issues, an important loss of economic productivity often ensues [14][15][16]; in one Ghanaian study, this amounted to 265 working days lost due to BUD [17].…”
Section: Introductionmentioning
confidence: 99%
“…24 Similarly, in these patients, anxio-depressive behaviors are noted in a context of family rejection. 25 Table 3 shows that the initial lesion type was not determinant in the outcome of patients' physical outcome (p=0.71). However, whether the type of scar carried by these patients or their neuro-orthopedic deformations was significantly influenced by the type of treatment received (Tables 4) (Table 5) (Table6).…”
Section: Discussionmentioning
confidence: 95%
“…A third study by Kpadonou et al [11] further documented differences of opinion about causality among a sample of 244 former BU patients treated at Allada Hospital and residing within a 100 km radius of the hospital. This study found that while a majority of adults and teens attributed BU to witchcraft, a majority of children perceived BU to have natural causes.…”
Section: Beninmentioning
confidence: 95%